Blood lactate levels of decathletes during competition - Beaulieu, P.; Ottoz, H.; Grange, C.; Thomas, J.; Bensch, C. (British Journal of Sports Medicine, 1995)
There are many detailed physiological profiles of athletes who participate in a wide variety of sporting activities but few data have been obtained on decathletes. This study defines some physiological characteristics of these athletes and measures capillary lactate concentrations [La(b)] during a laboratory test of progressive maximal exhaustion and the different events during competition. The treadmill test is similar to the 100 m, 400 m and 1500 m in terms of [La(b)] accumulation but only similar to the 1500 m in terms of velocity. The 400 m is the most demanding event with the greatest blood lactate accumulation (mean(s.d.) 16.38(2.36) mmol l-1). The [La(b)] at the end of the 110 m hurdles is significantly lower than in any other racing events (mean(s.d.) 6.96(1.32) mmol l-1) compared with mean(s.d.) 12.14(2.87) and mean(s.d.) 11.44(2.16) for the 100 m and 1500 m respectively. The [La(b)] after the long jump, the high jump and the pole vault are not significantly different (mean(s.d.) 5.30(2.23), 4.64(1.39) and 5.36(1.34) mmol l-1) respectively).